2013
DOI: 10.1111/acer.12218
|View full text |Cite
|
Sign up to set email alerts
|

Differential Striatal Dopamine Responses Following Oral Alcohol in Individuals at Varying Risk for Dependence

Abstract: Changes in striatal DA in response to alcohol ingestion may be a neurobiological marker of vulnerability to AUDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…This accords with our previous finding that beer flavor alone increased right NAcc DA in a similar population of heavy drinkers (Oberlin et al , 2013), and that (unexpected) intravenous ethanol intoxication increased left VST DA (Yoder et al , 2009). Previous reports showed bilateral VST DA increases resulting from ethanol CS and US presented together (Boileau et al , 2003; Setiawan et al , 2014; Urban et al , 2010), although in these studies, fruit juice was the tastant (not necessarily the preferred mixer), meaning that ethanol’s orosensory properties could have acted as a CS. If we regard these previous studies as concomitant alcohol CS and US presentation, these data comport with our current findings of bilateral NAcc DA release to combined alcohol CS and US presentation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This accords with our previous finding that beer flavor alone increased right NAcc DA in a similar population of heavy drinkers (Oberlin et al , 2013), and that (unexpected) intravenous ethanol intoxication increased left VST DA (Yoder et al , 2009). Previous reports showed bilateral VST DA increases resulting from ethanol CS and US presented together (Boileau et al , 2003; Setiawan et al , 2014; Urban et al , 2010), although in these studies, fruit juice was the tastant (not necessarily the preferred mixer), meaning that ethanol’s orosensory properties could have acted as a CS. If we regard these previous studies as concomitant alcohol CS and US presentation, these data comport with our current findings of bilateral NAcc DA release to combined alcohol CS and US presentation.…”
Section: Discussionmentioning
confidence: 70%
“…Other studies found no effect with IV alcohol (Yoder et al , 2007; Yoder et al , 2005), or found it only when alcohol was unexpected (Yoder et al , 2009). However, two RAC-PET studies reported bilateral VST DA release when social drinkers consumed alcoholic beverages orally, thus combining alcohol’s intraoral somatosensory CS effects with the US of intoxication (Boileau et al , 2003; Urban et al , 2010); a similar study of oral consumption reported bilateral VST DA release, but only in high-risk subjects (Setiawan et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
“…First, a distinctively high dopamine response was seen in impulsive substance users at elevated risk for addictions, as compared to low risk users, when they were tested with drug cues present (alcohol ingested with the beverage’s sight, smell, taste and touch) [120]. Second, and in striking contrast, exceptionally low dopamine release was observed in impulsive substance users at elevated risk for addictions when they were tested without drug cues present ( d -amphetamine tablets hidden in nondescript gelcaps) [114].…”
Section: Hyper- and Hypo-dopamine Activity Following The Initiation Omentioning
confidence: 99%
“…Some have been pointed out as addiction biomarkers or endophenotypes: working memory, behavioral inhibition (Iacono, Malone & McGue, 2008), error processing (Euser, Evans, Greaves-Lord, Huizink & Franken, 2013), anxiety-impulsivity traits like delayed reward discounting (MacKillop, 2013) and even subjective responses to alcohol (Setiawan et al, 2014). Neuroanatomical correlates of these predisposing factors have been described (Wetherhill et al, 2012;Seigneurie, Guérin Langlois & Limosin, 2013).…”
Section: Alcohol-related Brain Damage From Categories To Dimensionsmentioning
confidence: 99%